2015
DOI: 10.1186/s40164-015-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive mechanisms of human bone marrow derived mesenchymal stromal cells in BALB/c host graft versus host disease murine models

Abstract: BackgroundMesenchymal stromal cells (MSCs) are proven to have immunosuppressive functions via various mechanisms. These mechanisms were demonstrated by administering bone marrow derived human MSCs (hMSCs) to graft versus host disease (GVHD) murine models.MethodsBALB/c host mice were irradiated prior to receiving C57BL/6 donor T cell depleted bone marrow (TCDBM) cells (negative control) and donor CD4+ T lymphocyte with (treatment group) or without hMSCs (positive control). The presence of hMSCs in target tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Nomura et al published data, where patients with aGVHD and SOS showed higher levels of this cytokine ( 47 ). These data were also confirmed in vivo experiments in a murine model ( 48 ).…”
Section: Discussionsupporting
confidence: 73%
“…Nomura et al published data, where patients with aGVHD and SOS showed higher levels of this cytokine ( 47 ). These data were also confirmed in vivo experiments in a murine model ( 48 ).…”
Section: Discussionsupporting
confidence: 73%
“…A series of studies have demonstrated that the curative effects of MSCs on inflammatory diseases are related to their production of inducible nitric oxide synthase (iNOS), indoleamine 2,3-dioxygenase, tumor necrosis factor-inducible gene 6 (TSG-6), or prostaglandin E2 (PGE-2), whose expressions in MSCs are now known to be elicited by inflammatory cytokines, especially interferon gamma (IFN-g) (Galleu et al, 2017;Lee et al, 2009;Né meth et al, 2009;Ren et al, 2008Ren et al, , 2009. Interestingly, it has been reported that human MSCs could effectively ameliorate autoimmune diseases in mice (Galleu et al, 2017;Robles et al, 2015;Yañ ez et al, 2006). It is worth noting that mouse IFN-g does not bind to human receptors, and human cells do not persist in the mouse body (Hemmi et al, 1992;Su et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Together with another research group, we have found that systemic infusion of human MSCs can alleviate the severity of murine aGvHD manifestation and improve survival 54 . We utilized irradiated BALB/c host mice to receive C57BL/6 donor T-cell-depleted bone marrow with or without donor CD4+ T lymphocytes as controls.…”
Section: Pre-clinical In Vivo Evidencementioning
confidence: 84%